Martensitic transformation in freestanding and supported Cu–Al–Ni thin films obtained at low deposition temperatures - Morán, Mauricio Javier (2016)
In order to use the shape memory alloy Cu-Al-Ni in micro-actuators, freestanding thin films with martensitic transformation are required. Here we show that freestanding Cu-Al-Ni thin films with L21 structure, martensitic transformation and shape memory effect can be obtained using iron as a sacrificial layer. The Cu-Al-Ni films with best performance are obtained at deposition temperatures between 533 K and 563 K. The Fe layer can afterwards be removed selectively by electrochemical etching.